TEORÍA SOCIAL COMO «MÚSICA DE PALABRAS». ELEMENTOS DE ANÁLISIS (QUE NO SERÁN BIENVENIDOS) EN TORNO AL MARXISMO EDULCORADO DEL VENDEHÚMOS ACADEMICUS S. ŽIŽEK - Haba, Enrique Pedro (Universidad de Costa Rica, 2021)
This paper offers an analytic-realistic scrutiny about the well known debate PetersonŽižek, “Hapiness: Capitalism vs. Marxism”. Such examination makes it evident that Žižek’s ways to approach (essentialism, intellectualist fallacy, etc.) suffer from oversimplification, great indeterminacy (empty formulae) and, in general, theoretical escapism. Anyhow, this was a pseudo-‘debate’: there were no fundamental contradictions, strictly speaking, between what was alleged by those two speakers in their initial expositions (“vorbeireden”); and both agreed even about the paratheological foundations towards which they directed their main attention on the second part of that event. Finally, some observations are added regarding certain further considerations by Žižek: his harangues about hopeful futurology (and as usual in the mood wordmusic), now based on the current work of covid-19 —very welcome for it should bring the salvific definitive globalist social engineering, managed through the sovereign imperium of un officers.